Synthesis and characterization of PtRuMo/C nanoparticle electrocatalyst for direct ethanol fuel cell - Wang, Z.B.; Yin, G.P.; Lin, Y.G.
This research aims at enhancement of the performance of anodic catalysts for the direct ethanol fuel cell (DEFC). Two distinct DEFC nanoparticle electrocatalysts, PtRuMo/C and PtRu/C, were prepared and characterized, and one glassy carbon working electrode for each was employed to evaluate the catalytic performance. The cyclic-voltammetric, chronoamperometric, and amperometric current-time measurements were done in the solution 0.5 mol L-1 CH3CH2OH and 0.5 mol L-1 H2SO4. The composition, particle sizes, lattice parameters, morphology, and the oxidation states of the metals on nanoparticle catalyst surfaces were determined by energy dispersive analysis of X-ray (EDAX), X-ray diffraction (XRD), transmission electron micrographs (TEM)and X-ray photoelectron spectrometer (XPS), respectively. The results of XRD analysis showed that both PtRuMo/C and PtRu/C had a face-centered cubic (fcc)structure with smaller lattice parameters than that of pure platinum. The typical particle sizes were only about 2.5 nm. Both electrodes showed essentially the same onset potential as shown in the CV for ethanol electrooxidation. Despite their comparable active specific areas, PtRuMo/C was superior to PtRu/C in respect of the catalytic activity, durability and CO-tolerance. The effect of Mo in the PtRuMo/C nanoparticle catalyst was illustrated with a bifunctional mechanism, hydrogen-spillover effect and the modification on the Pt electronic states
Keywords: DIRECT ETHANOL FUEL CELL; PTRUMO/C NANOPARTICLE ELECTROCATALYST; PTRU/C NANOPARTICLE ELECTROCATALYST; ETHANOL ELECTROOXIDATION